A forgotten sour cherry pest, the stone fruit weevil (Anthonomus /Furcipes/ rectirostis L.) appeared again - Szarukán, István (Acta Agraria Debreceniensis, 2011)
The stone fruit weewil (Anthonomus rectirostris L.) has been known as the kernel pest of the wild cherry in Hungary. There have been no data about its harm on sour cherry (Prunus cerasus L.) in our country, yet. 5-10% of stone infection has been observed on some sour cherry trees (cultivars: Debreceni bőtermő, Újfehértói fürtös) in the eastern side of an orchard at Debrecen-Józsa adjacent to a wood in early July 2011. The damage can be in connection with the fact that the yield has not been harvested for years.